The Effectiveness of Unguided Internet-Based Cognitive Behavioral Therapy for Tinnitus for Patients with Tinnitus Alone or Combined with Hyperacusis and/or Misophonia: A Preliminary Analysis - Aazh, Hashir; Taylor, Lauren; Danesh, Ali A.; Moore, Brian C. J. (Journal of the American Academy of Audiology, 2022)
Background In the United Kingdom, audiologist-delivered cognitive behavioral therapy (CBT) is a key intervention to alleviate the distress caused by tinnitus and its comorbid hyperacusis. However, the availability of face-to-face CBT is limited, and such therapy involves significant costs. CBT provided via the internet provides a potential solution to improve access to CBT for tinnitus.Purpose The aim was to perform a preliminary assessment of the effect of a specific program of nonguided internet-based CBT for tinnitus, denoted iCBT(T), in alleviating the problems caused by tinnitus alone or tinnitus combined with hyperacusis.Research Design This was a retrospective cross-sectional study.Study Sample The data for 28 people with tinnitus who completed the iCBT(T) program and answered a series of questions about their tinnitus and hearing status were included in the study. Twelve patients also reported having hyperacusis (including five also with misophonia).Data Collection and Analysis The iCBT(T) program has seven self-help modules. Anonymous data were collected retrospectively from patients' answers to the questions in the iCBT(T) initial and final assessment modules. Questionnaires administered within the iCBT(T) program were: 4C Tinnitus Management Questionnaire (4C), Screening for Anxiety and Depression in Tinnitus (SAD-T), and the CBT Effectiveness Questionnaire (CBT-EQ).Results Responses to the 4C showed a significant improvement from pre- to posttreatment, with a medium effect size. The mean improvement was similar for those with and without hyperacusis. Responses to the SAD-T questionnaire also showed a significant improvement from pre- to posttreatment with a medium effect size. The improvement was significantly greater for participants with tinnitus alone than for participants who also had hyperacusis. For both the 4C and the SAD-T, the improvements were not significantly related to age or gender. Participants' views of the effectiveness of the iCBT(T) program were assessed using the CBT-EQ. The mean score was 50 out of a maximum of 80, indicating moderately high effectiveness. CBT-EQ scores did not differ for those with and without hyperacusis.Conclusion Based on this preliminary analysis, the iCBT(T) program showed promising results in improving the ability to manage tinnitus and decreasing symptoms of anxiety and depression. Future studies with larger samples and control group(s) are required to further assess various aspects of this program.
Keywords: tinnitus; CBT; telehealth; hyperacusis; misophonia